Hydrodynamic activation of heavy oil residues - V. B. Terenteva; B. V. Peshnev; A. I. Nikolaev (Тонкие химические технологии, 2021)
Objectives. Recently, there has been a tendency to increase the volume of high-viscosity heavy oils in the total volume of oil produced. The processing of these oils requires new technological approaches. This task is closely related to the need to increase the depth of oil refining. Among the approaches proposed to solve these problems, mechanochemical activation, which is based on the cavitation effect produced by ultrasonic or hydrodynamic methods, has been suggested. This study evaluated the effects of cavitation in increasing the depth of oil refining.Methods. Straight-run and “secondary” oil products were used as raw materials: vacuum gas oil, catalytic cracking gas oil, and fuel oil. Activation was carried out in a high-pressure disintegrator. The principle of operation was to compress the oil product and then pass it through a diffuser. When the oil was passed through the diffuser, there was a sharp pressure release to atmospheric pressure, which caused cavitation in the hydrodynamic flow. The pressure gradient on the diffuser and the number of processing cycles ranged from 20 to 50 MPa and 1 to 10, respectively. The density, refractive index, and the fractional composition of petroleum products were determined using standard and generally accepted methods.Results. This paper reports the influence of mechanochemical activation of petroleum products on their physical and chemical characteristics. An increase in the pressure gradient and the number of processing cycles leads to a decrease in the boiling point of the petroleum products and their density and an increase in the yield of fractions that boil off below 400 °C. The yield of the fractions with boiling points of 400–480 °C and the remainder were reduced. The density and refractive index of fractions with boiling points up to 480 °C decreased, and the density of the residue increased. The effects of cavitation (an increase in the yield of fractions with boiling points up to 400 °C and a decrease in the density of the petroleum products) increased with increasing pressure gradient and the number of processing cycles.Conclusions. The changes in the density, boiling point, and the yield of fractions increased with increasing the pressure from 20 to 50 MPa and the number of hydrodynamic cavitation cycles from 1 to 5. Increasing the number of processing cycles to more than five had little additional effect. The effects of cavitation increased with increasing initial density of the oil product. The average molecular weight of these fractions was estimated from the densities and boiling points of individual fractions of the petroleum products. The calculation confirmed the assumption regarding the course of cracking reactions of petroleum products under the influence of cavitation and indicates the course of the compaction processes.